Synthesis, Characterization and Coordinating Behaviour of Aminoalcohol Complexes with Transition Metals - K. Majid; R. Mushtaq; S. Ahmad (E-Journal of Chemistry)
The complexation of aminoalcohols with various transition metal and metal complexes have long and varied history. Since these complexes have found applications in various fields, the coordinating behaviour of these complexes should be investigated more precisely, in view of contradictory reports regarding coordinating behaviour of aminoalcohols with transition metals. This article is a review of findings of various investigations carried out from time to time.